2014
DOI: 10.5296/jse.v4i1.4154
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Organizational Innovativeness Types and Organizational Effectiveness in Private Universities in Iran

Abstract: Empirical evidences indicate that if institutions of higher education are to survive and achieve long-run viability, they must be effective. Organizational innovativeness is viewed as an important factor for improving the organizational effectiveness in these organizations. The aim of this study was to examine the correlations between organizational innovativeness types and organizational effectiveness. The method used in the study was survey research. Based on cluster sampling method, 485 full time faculty me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 26 publications
(7 reference statements)
3
8
0
Order By: Relevance
“…(2016), Ogbeibu et al (2018b), andGupta (2011) argued that OC's that are hierarchical often negatively influence employee creativity by inhibiting creative ideas exchange. Moreover, this notion was supported by Ashraf et al (2013), whose findings concerning the foundations of employee creativity confirmed that the hierarchy OC negatively affects it. We thus posited as follows:…”
Section: Hypothesis 1a the Adhocracy Oc And Employee Creativity Are P...mentioning
confidence: 76%
See 1 more Smart Citation
“…(2016), Ogbeibu et al (2018b), andGupta (2011) argued that OC's that are hierarchical often negatively influence employee creativity by inhibiting creative ideas exchange. Moreover, this notion was supported by Ashraf et al (2013), whose findings concerning the foundations of employee creativity confirmed that the hierarchy OC negatively affects it. We thus posited as follows:…”
Section: Hypothesis 1a the Adhocracy Oc And Employee Creativity Are P...mentioning
confidence: 76%
“…In the CTIC, Amabile (1997) advocate that employees are capable of making at least moderate creative efforts regardless of domain and time. Hence, some studies (Ashraf, Kadir, Pihie & Rashid., 2013) grounded on the concept of employee creativity have also found that the features of market OC are positively associated with employee creativity. We therefore formulated the following hypothesis: Hypothesis 1c.…”
Section: Hypothesis 1a the Adhocracy Oc And Employee Creativity Are P...mentioning
confidence: 99%
“…Organizations that need to be innovative have to transform their organizational culture so that it has pro-innovative character. And that can be found in the work of [25], the researchers state that creativity, innovation, and inventiveness are crucial for the survival and success of today's knowledge-based organization. Moreover, the research illustrates the five determinants of organizational culture that support innovation and creativity.…”
Section: Resultsmentioning
confidence: 99%
“…The results of [25], show significant positive relationships between three types of organizational culture (which are: adhocracy, the market, and the clan) and organizational innovativeness. While the hierarchy culture manifests a non-significant correlation with organizational innovativeness, besides, the adhocracy culture contributed most to predicting organizational innovativeness.…”
Section: Advances In Social Science Education and Humanities Researcmentioning
confidence: 93%
“…Generally, scholars uniformly indicate that a significant and positive relationship exists between innovation and superior organizational performance (Ashraf, Kadir, Pihie, & Rashid, 2014;Camisón & López, 2010;Chen, Lin, & Yang, 2011). Unfortunately, however, Battor and Battor (2010) have indicated that the failure rate of new products is between 40% and 75%.…”
Section: Introductionmentioning
confidence: 99%